Homeless management during movement control order due to COVID-19 pandemic : experience from Federal Territory Kuala Lumpur, Malaysia - Haliza Abdul Manaf; Rozita Arifin; Mohd Rizal Abdul Manaf (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Malaysia has been hit by COVID-19 pandemic since 2020 and this problem also affects countries around the world. This COVID-19 infection does not distinguish age, gender, educational and financial status. Homeless people are also not exempt from being infected with COVID-19, especially when the government implements the Movement Control Order, particularly these people who have no permanent home. This article describes the activities carried out by the government agencies, especially from the Ministry of Health Malaysia, Department of Social Welfare, National Anti-Drugs Agency, Immigration Department of Malaysia, as well as other non-governmental agencies in the Federal Territory of Kuala Lumpur on homeless people during movement control orders. It is hoped that this shared experience can be a guide to government agencies, non-governmental organizations, private sectors and individuals in other states to manage this underprivileged group, especially during the ongoing COVID-19 pandemic.